SEMIOTIC ANALYSIS OF MOON KNIGHT EPISODE 5: ASYLUM USING PEIRCE'S THEORY OF SIGN - Firstiyanti, Aulia Haris; Sentana, Aswarini; Wulandari, Ratna (Journal of Language and Literature, 2025)
This research presents a semiotic analysis in an episode of a television series. The objective of this research is to analyze symbols in Moon Knight Episode 5: Asylum using Pierce's triadic model of signs, which consists of Representamen (the form of the sign), Object (the subject the sign refers to), and Interpretant (the meaning generated in the observer's mind). The method used in this research is a descriptive qualitative method through library research. Key symbolic elements, such as the asylum, the goddess Taweret, and the feather of the truth, are examined as signs that carry layered meanings related to identity, guilt, healing, and rebirth. The researchers found and analyzed 10 symbols in the studied episode. This analysis reveals how the episode constructs psychological, mythological, and moral meanings through visual and narrative symbolic signs to represent the main character's inner emotional states. Furthermore, the analyzed episode serves as a powerful example of how visual narration and semiotic structures can merge to explore mental health, identity fragmentation, and the quest for self-acceptance.